Development of MOKASEMAR Media-Based PMRI to Improve Problem Solving and Critical Thinking Skills of Fifth Grade Students at SDN Karanganyar 01 - Bunga Muawanah Munawar; Nursiwi Nugraheni (FKIP - Universitas Riau, 2026)
The goal of this research was to develop a MOKASEMAR media to improve the critical thinking and problem-solving abilities of fifth-grade students on the subject of numbers up to 1.000.000. R&D using an ADDIE design was the methodology employed. The validation score from the experts was 93.18% from media experts, 93.75% from material experts, 95.8% from language experts, and 100% from teachers and students, with a very feasible category. The significance level (2-tailed) of the paired t-test is approximately 0,000, indicating that the post-test score for problem-solving and critical thinking skills is higher than the pre-test score. Furthermore, the control class's N-Gain scores for critical thinking and problem-solving abilities were 0.6209 and 0.6553, which are classified as moderate and quite effective. In addition, the experimental class's N-Gain scores were 0.6828 and 0.6993, which are classified as moderate and quite effective. According to the findings, the MOKASEMAR media has successfully improved critical thinking and mathematical problem-solving abilities in whole numbers up to 1.000.000.